Is It Necessary to Remove the Implants After Fixation of Thoracolumbar and Lumbar Burst Fractures Without Fusion? A Retrospective Cohort Study of Elderly Patients - Xu, Xiangyu; Cao, Yuan; Fan, JiXing; Lv, Yang; Zhou, Fang; Tian, Yun; Ji, Hongquan; Zhang, Zhishan; Guo, Yan; Yang, Zhongwei; Hou, Guojin (Frontiers in Surgery, 2022)
Objective: Fractures of the thoracolumbar spine are the most common fractures of the spinal column. This retrospective cohort study aimed to determine whether it is necessary to remove implants of patients aged over 65 years after the fixation of thoracolumbar and lumbar burst fractures without fusion. Methods: This retrospective cohort study included 107 consecutive patients aged ≥65 years without neurological deficits, who underwent non-fusion short posterior segmental fixation for thoracolumbar or lumbar burst fractures. Outcome measures included the visual analog score (VAS), Oswestry Disability Index (ODI), residual symptoms, complications, and imaging parameters. Patients were divided into groups A (underwent implant removal) and B (implant retention) and were examined clinically at 1, 3, 6, and 12 months postoperatively and annually thereafter, with a final follow-up at 48.5 months. Results: Overall, 96 patients with a mean age of 69.4 (range, 65–77) years were analyzed. At the latest follow-up, no significant differences were observed in functional outcomes and radiological parameters between both groups, except in the local motion range (LMR) (P = 0.006). Similarly, between preimplant removal and the latest follow-up in group A, significant differences were found only in LMR (P <0.001). Two patients experienced screw breakage without clinical symptoms. Significant differences were only found in operation time, blood loss, ODI, and fracture type between minimally invasive group and open group. Conclusions: Similar radiological and functional outcomes were observed in elderly patients, regardless of implant removal. Implant removal may not be necessary after weighing the risks and benefits for elderly patients. Patients should be informed about the possibility of implant breakage and accelerating degeneration of adjacent segments in advance.